Molecular characterization of the malaria vector Anopheles barbirostris van der Wulp in Sri Lanka - Gajapathy, Kanapathy; Jude, Pavilupillai J.; Goodacre, S.L.; Peiris, Lalanthika B.S.; Ramasamy, Ranjan; Surendran, Sinnathamby N. (BioMed Central, 2014)
Background: Anopheles barbirostris is a vector of malaria in Sri Lanka. The taxon exists as a species complex in the Southeast Asian region. Previous studies using molecular markers suggest that there are more than 4 distinct clades within the An. barbirostris complex in Southeast Asia. The present study characterizes Sri Lankan An. barbirostris using mtDNA cytochrome oxidase subunit I (COI) and ribosomal RNA internal transcribed spacer 2 (ITS2) gene sequences.